Excess Mortality Attributable to COVID-19 Among Assisted Living Residents. (17th December 2021) - Thomas, Kali; Zhang, Wenhan; Dosa, David; Carder, Paula; Sloane, Philip; Zimmerman, Sheryl
Abstract: This study examines the excess mortality attributable to COVID-19 among a national cohort of assisted living (AL) residents. To do this, we compare the weekly rate of all-cause mortality during 1/1/20-8/11/20 with the same weeks in 2019 and calculated adjusted incidence rate ratios (IRRs) and 95% confidence intervals (CIs). All-cause mortality rates, nationally, were 14% higher in 2020 compared with 2019 (mean, 2.309 vs. 2.020, respectively, per 1000 residents per week; adjusted IRR, 1.169; 95% CI 1.165-1.173). Among the 10 states with the highest community spread, the excess mortality attributable to COVID-19 was 24% higher, with 2.388 deaths per 1000 residents per week in 2020 during January-August vs 1.928 in 2019 (adjusted IRR, 1.241; 95% CI 1.233-1.250). These results suggest that AL residents suffered excess mortality due to COVID-19.